ISLAMIC CROWDFUNDING IN INDONESIA: TECHNOLOGY CONTINUANCE PERSPECTIVE - Koeswandana, Noorfaiz Athallah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
This study aims to examine the factors influencing the continuance intention to use Islamic crowdfunding platforms in Indonesia by applying an extended Technology Continuance Theory (TCT). The proposed model includes six constructs: confirmation, perceived usefulness, perceived value, perceived risk, user satisfaction, and continuance intention. Data were collected from active users of Islamic crowdfunding platforms and analysed using structural equation modelling. The results reveal that confirmation significantly affects perceived usefulness and user satisfaction. Additionally, perceived usefulness, perceived value, and perceived risk significantly influence user satisfaction, which in turn positively impacts continuance intention. These findings underscore the importance of meeting user expectations, enhancing platform value, and minimizing risk to foster long-term engagement. The study contributes theoretically by extending TCT with perceived value and risk in the context of Islamic financial technology, providing a more comprehensive understanding of post-adoption behavior in faith-based platforms. Practically, the results offer valuable insights for platform developers and policymakers to improve service design, trust-building, and regulatory support. However, the findings are limited by the studys cross-sectional design and single-country scope, suggesting future research should adopt longitudinal and cross-cultural approaches to enhance generalizability.